ANALISIS CUSTOMER SATISFACTION INDEX (CSI) TERHADAP KINERJA PEDAGANG SAYURAN DI PASAR TRADISIONAL KABUPATEN SUKOHARJO - Ratih Dwi Kartikasari (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
Consumption of vegetables needs to be done to fulfill daily nutrition. The traditional market is one of the retail markets that provides fresh vegetables and is easily found in various regions. Marketing mix is ??one of the marketing strategies applied by traders to find out and assess customer satisfaction. The purpose of this study is to determine consumer satisfaction in shopping for vegetables in traditional markets. The method used is the Customer Satisfaction Index (CSI) analysis. The research location is in Sukoharjo District with 60 respondents of traditional market vegetable consumers with quota sampling technique. Based on the results of the study note that the CSI value of all variables is 77%, which means that respondents are satisfied with the performance of vegetable merchants in traditional markets in Sukoharjo Regency. The sequence of variables that gives the highest to lowest satisfaction according to consumers is the product, price, people, physical evidence, promotion, place, and process variables.